Lesion characteristics affecting yield of electromagnetic navigational bronchoscopy. (April 2021) - Bellinger, Christina; Poon, Rita; Dotson, Travis; Sharma, Deepankar
Abstract: Rationale: Electromagnetic navigational bronchoscopy (ENB) is an important, minimally invasive diagnostic tool for malignant and benign peripheral lung lesions, offering lower complication risks than transthoracic needle aspirations. As a relatively new technology, the best sampling modality and lesion characteristics for ENB has yet to be determined. We evaluated the sensitivity and diagnostic yield of different sampling modalities (needle aspiration, brush biopsy, transbronchial forceps biopsies) and radiographical lesion characteristics by Tsuboi classification. We also evaluated the difference in yield and sensitivity with the addition of radial probe EBUS to augment ENB. Methods: We completed a retrospective chart review of all patients that had ENB performed at our institution since its implementation in 2011. We reviewed the lesion size, location, Tsuboi classification, cytology, pathology results and analyzed biopsy specimen tool types. Results: We included a total of 248 patients who had ENB performed between 2011 and 2018. Average age was 67 years and 50% female. A total of 270 lesions were targeted with a mean size of 24 ± 12 mm. Sensitivity for malignancy was 59.2% with a diagnostic yield of 72.3%. Sensitivity and diagnostic accuracy trended higher with combined sampling modalities (brush and transbronchial needle aspiration and forcep biopsy). Lesions with type I and type II Tsuboi classification of bronchus sign had higher sensitivity compared to type III classification (67.9% [n = 101 type I], 64.6% [n = 65 type II], 37.9% [n = 36 type III]), p = 0.01 and p = 0.04. Conclusion: For navigation bronchoscopy, sensitivity is higher in bronchus sign lesions that end directly into lesion (Tsuboi type I) and travel through malignant lesions (Tsuboi type II) compared to tangentially circumventing the lesion (Tsuboi type III). Highlights: Bronchus sign has been a proven indicator of higher yields with navigation bronchoscopy. Sensitivity is higher in bronchus signs that end into the malignant lesion (Tsuboi type I) or travel through it (Tsuboi type II). Sensitivity is lower in bronchus signs that tangentially circumventing malignant lesions (Tsuboi type III).